Strategi Perencanaan Klinik Agribisnis di Kabupaten Jombang - Suci, Ririn Kurnia (Universitas Islam Kadiri, 2024)
An agribusiness clinic is an institution that plays a role as a supplier of agricultural technology innovations. The concept of an agribusiness clinic has existed in Jombang Regency in 2008 as a part of Primatani. The Agricultural Services are re-launching it as a major program in agricultural development in Jombang in 2022. The aims of this research are to describe the transformation of the former concept into a new agribusiness clinics concept, to know the support systems of the external and internal environment and the planning strategy appropriately in the implementation of agribusiness clinics in Jombang. The data analysis that is used is qualitative analysis and analysis of EFE, IFE, IE matrix, SWOT matrix and QSPM. The results of this study are the agribusines clinic in Jombang has undergone a transformation. The new concept is the development of the former concept which encourage further development of the dissemination pattern and its implementation concept. The support system of the main external environment is the increasing need for healthy and quality agricultural products. While the main support system of the internal environment is the existence of extension institutions at the district level, which is the UPT Implementing Agricultural Extension and efforts to increase the capacity of farmers and extension workers. The appropriate planning strategy is strengthening the duties and functions of BPP as the center for implementing agribusiness clinics.